NIMG-01. INTEROBSERVER VARIABILITY OF THE REVISED IMAGING SCORECARD FOR LEPTOMENINGEAL METASTASIS: A JOINT EORTC BRAIN TUMOR GROUP AND RANO EFFORT. (12th November 2021) - Le Rhun, Emilie; Devos, Patrick; Winklhofer, Sebastian; Lmalem, Hafida; Brandsma, Dieta; Pérez-Larraya, Jaime Gállego; Castellano, Antonella; Compter, Annette; Dhermain, Frederic; Franceschi, Enrico; Forsyth, Peter; Furtner, Julia; et al.
Abstract: BACKGROUND: Validation of the 2016 LANO MRI scorecard for leptomeningeal metastasis failed for multiple reasons. The objective of this joint EORTC Brain Tumor Group and RANO effort was to validate the feasibility of the revised MRI scorecard for assessing response in leptomeningeal metastasis. METHODS: Coded paired cerebrospinal MRI of 20 patients with leptomeningeal metastases from solid cancers at baseline and follow-up after treatment and instructions for assessment were provided via the EORTC imaging platform. The kappa coefficient (K) was used to evaluate inter-observer pairwise agreement. Statistical analyses were performed using SAS V9.4 software (Cary, NC). The sponsor of the study was the University Hospital Zurich (2018-00192). RESULTS: Thirty-five raters participated, including 9 neuroradiologists, 17 neurologists, 4 radiation oncologists, 3 neurosurgeons and 2 medical oncologists. Among leptomeningeal metastases-related items at baseline, the best median concordance was noted for hydrocephalus (K=0.63), and the worst median for spinal linear enhancing disease (K=0.46). The median concordance for overall response was moderate (K=0.44). Notably, the interobserver agreement for the presence of parenchymal brain metastases at baseline was minimal (K=0.29). Significant differences were observed when considering the specialty of the raters. Only 394 of 700 ratings (56%) were fully completed. Among 394 fully completed ratings, perfect concordance was noted in 293 ratings (74%) when comparing the overall response according to the guidelines provided in the scorecard and the overall response provided by the raters. The main discordances were noted for partial response according to the rater versus stable disease according to the guidelines (n=44), followed by progression according to the raters versus stable disease according to the guidelines (n=23). CONCLUSION: Electronic case report forms with "blocking solutions" are probably required to enforce completeness and quality of scoring. These results confirm the necessity of central review and the need for training of MRI assessment in clinical trials.